2017
DOI: 10.1093/cid/cix342
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica serovar Typhi Producing CTX-M-15 Extended Spectrum β-Lactamase in the Democratic Republic of the Congo

Abstract: We report a typhoid fever case with a Salmonella enterica serovar Typhi isolate showing extended spectrum β-lactamase (ESBL) production in the Democratic Republic of the Congo. Whole genome sequencing revealed that the strain carried a plasmid-mediated CTX-M-15 ESBL gene and did not belong to the dominant H58 Salmonella Typhi clade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 13 publications
3
36
2
Order By: Relevance
“…The Indian isolates were reported to carry IncA and IncX3 plasmids and harboring blaSHV-12, blaCMY-2, blaDHA-1 and blaTEM-1B determinants [18,19]. An S. Typhi isolates encoding blaCTX-M15 gene on an IncY plasmid was recovered from the Democratic Republic of Congo [9]. Few other studies have reported the blaCTX-M producing S. Typhi isolates from Nigeria, Japan, and Southern India as well as from the travelers having a travel history to Iraq and Guatemala [5,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Indian isolates were reported to carry IncA and IncX3 plasmids and harboring blaSHV-12, blaCMY-2, blaDHA-1 and blaTEM-1B determinants [18,19]. An S. Typhi isolates encoding blaCTX-M15 gene on an IncY plasmid was recovered from the Democratic Republic of Congo [9]. Few other studies have reported the blaCTX-M producing S. Typhi isolates from Nigeria, Japan, and Southern India as well as from the travelers having a travel history to Iraq and Guatemala [5,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The extended-spectrum β-lactamase (ESBL) producing S. Typhi strains were quite uncommon from the introduction of cephalosporins till the first decade of the 21st century and were reported only from few studies from Asian countries or the patients with a history of travel to that region [5][6][7][8]. The ESBLs are known to confer cephalosporin resistance; although were previously uncommon among Salmonella enterica serovar Typhi strains and this transfer is facilitated especially if these resistant determinates are associated with transposon or plasmids, for example, blaCTXM-15 [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, in parts of sub-Saharan Africa (SSA), non-typhoidal Salmonella (NTS) is a major cause of deadly bacteremia [41] . For instance, studies from Kenya have reported that community-acquired NTS is among the top three causes of death among children [43][44][45] . Non-typhoidal Salmonella resistance to fluoroquinolones was reported to be in the 3.8-6.1% range in Congo [23,46,47] .…”
Section: Multidrug-resistant Salmonellamentioning
confidence: 99%
“…Enteric fever is characterized by disseminated infection and septicaemia. Its mortality has been significantly reduced by implementation of appropriate antibiotic treatment but the increase in beta-lactam and fluoroquinolone resistance of Salmonella strains is a growing public health problem [3][4][5][6]. Depending on the immune status of the patient, NTS can also cause extraintestinal and bloodstream infections with various manifestations such as meningitis, septic arthritis, abscesses and osteomyelitis [7,8].…”
Section: Introductionmentioning
confidence: 99%